2007
DOI: 10.1007/s11606-007-0160-1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Racial Bias Among Health Care Providers: Lessons from Social-Cognitive Psychology

Abstract: The paper sets forth a set of evidence-based recommendations for interventions to combat unintentional bias among health care providers, drawing upon theory and research in social cognitive psychology. Our primary aim is to provide a framework that outlines strategies and skills, which can be taught to medical trainees and practicing physicians, to prevent unconscious racial attitudes and stereotypes from negatively influencing the course and outcomes of clinical encounters. These strategies and skills are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
351
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(358 citation statements)
references
References 100 publications
2
351
0
5
Order By: Relevance
“…However, when patients are upset, physicians sometimes respond in problematic ways, ranging from avoidance, to anger, to using stereotypes as a form of distancing. [68][69][70] And studies show that physicians' specific professional biases may lessen their ability to see patients' situations clearly, for example, when they are overly influenced by the memory of a rare bad outcome. 65,71 Therefore, physicians are likely to better address patients' emotional needs if they incorporate tools for reflective self-awareness into their practices.…”
Section: Emotional and Social Influences On Affective Forecastingmentioning
confidence: 99%
“…However, when patients are upset, physicians sometimes respond in problematic ways, ranging from avoidance, to anger, to using stereotypes as a form of distancing. [68][69][70] And studies show that physicians' specific professional biases may lessen their ability to see patients' situations clearly, for example, when they are overly influenced by the memory of a rare bad outcome. 65,71 Therefore, physicians are likely to better address patients' emotional needs if they incorporate tools for reflective self-awareness into their practices.…”
Section: Emotional and Social Influences On Affective Forecastingmentioning
confidence: 99%
“…The first step in minimizing any potential negative effects of implicit bias is increasing awareness. Awareness of unwanted implicit stereotypes and being motivated to counteract them—or creating structures that minimize their effects—may help ensure that implicit bias does not overtly influence behavior 34, 60. Implicit bias is modifiable in experimental settings using counterstereotyping exercises; however, these methods have not been applied in a clinical setting 61.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess et al 7 suggested that increasing provider confidence and ability to interact with socially dissimilar patients can increase opportunity to create positive associations to replace automatic negative stereotypes. There is a growing body of research supporting the positive impact of cultural competency training including field experience with community health and perspective taking exercises on intermediate outcomes such as knowledge, attitudes, and skills of health professionals.…”
Section: ) Increase Opportunities For Positive Interactionmentioning
confidence: 99%